New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

Chalcopyrite as an indicator of uranium mineralization in the Qigequan deposit, western Qaidam Basin: Constraints from mineralogy, geochemistry, and sulfur isotopes - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Wen-Yi Wu; Chen Zhang; Zhe Chi; Zhi-Lin Cheng; Bin Guo; Yi-Fan Gao (Journal of Geochemical Exploration, 2026)

Accelerating iterative convergence of high-fidelity Monte Carlo neutronics and thermal-hydraulics coupling simulations using dynamic mode decomposition with global normalization correction - Binhang Zhang; Changxiao Guan; Dongfang Fan; Xianbao Yuan; Qingwen Xiong; Sen Zhang; Yonghong Zhang (Computer Physics Communications, 2026)

Construction of a porous-ionic-polymer encapsulated Rh-TPPTS catalyst for regioselective hydroformylation - Sen Feng; Cunyao Li; Guifa Long; Guangjun Ji; Xiaofeng Ma; Benhan Fan; Hong Wei; Xinyuan Liu; Yang Zhao; Miao Jiang; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2026)

Low-molecular-weight soybean peptides alleviate hyperuricemia in mice through xanthine oxidase inhibition, gut microbiota modulation, and metabolic reprogramming - Chen Wang; Jin Qian; Jiajing Liao; Lijuan Rao; Sen Mei; Bing Yuan; Tingting Geng; Haowei Fan; Guiming Fu; Yin Wan (Food Bioscience, 2026)

Hormesis induced by lithium exposures influenced the effects of maternal age at reproduction on offspring quality of Brachionus calyciflorus: A multigenerational study - Fan Gao; Ziyang Zhang; Sen Feng; Tianyi Du; Meng Li; Lingyun Zhu; Bin Chu; Zhizhong Li; Xinfeng Cheng; Xianling Xiang (Aquatic Toxicology, 2026)

Menaquinone-4 protects CD8+ T cells from ferroptosis to enhance anti-tumor immunity - Jiarong Wang; Wen Wang; Simiao Fan; Liyun Liang; Huaibin Hu; Zenqing Song; Yu Zhang; Jiamei Zhang; Wanying Xiao; Biyu Zhang; Yaxin Li; Liang Luo; et al. (Science China Life Sciences, 2026)

Extending Zipf's law: hierarchical scaling analysis and the dynamics of city-level CO2 emissions in China - Sen Liang; Ke Wang; Qiu Jin; Jianjun Zhang; Zhenlin Fan; Iskid Jacquet; Bangning Fu (Sustainable Cities and Society, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Construction of PtIn@S-1 || hollow H-ZSM-5 composite catalyst for propane aromatization - Zhao Ma; Sen Wang; Shiying Li; Zhikai Li; Han Wang; Qi Li; Baichao Li; Dezhi Shi; Pengfei Wang; Mei Dong; Weibin Fan (Fuel, 2026)

A novel pretreatment strategy for non-aggressive chromium speciation based on a sole bifunctional magnetic ion-imprinted nanocomposite with mild freezing grinding - Yi-Fan Pan; Sen Zhang; Jing Yang; Xiao-Bing Cui; Hong-Zhen Lian (Analytica Chimica Acta, 2026)

Experimental Verifications and Applications of Discontinuous Deformation Analysis in Block-Type Rock Slope Failure and Movement Mechanisms - Guoyang Liu; Shouyi Luo; Sen Zhang; Ke Ma; Wu Bo; He Fan; Zewen Dong (Rock Mechanics and Rock Engineering, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Anti-leukemia steroidal saponins from Paris polyphylla var. yunnanensis - Yu Zhang; Yu-Chen Zhang; Yu-Chen Fan; Chen-Sen Xu; Hao-Lin Yu; Chao Wang; Jing Zhang; Yi-Lin Liu; Yi-Bo Shen; Chao Liu; Jin-Yue Sun; Jin-Zhong Hu; et al. (Phytochemistry, 2026)

Mechanisms of oat dough adhesion modulated by moisture-controlled roasting: The role of aqueous extracts - Binghua Sun; Ruige Yu; Xiaojie Qian; Fan Yang; Sen Ma; Chong Liu; Xiaoxi Wang (Food Hydrocolloids, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

The interactive effects of roasting degree and lipid content on the gas retention capacity in fermented oat dough - Fan Yang; Wenhua Ma; Ruige Yu; Binghua Sun; Xiaojie Qian; Cong Sun; Chong Liu; Sen Ma; Xiaoxi Wang (Food Research International, 2026)

Novel antioxidant peptides identified from wheat germ protein: Structure-activity relationships, stability, and cytoprotective ability - Ling Fan; Xiaolin Yang; Sen Ma; Xinrui Zhang; Jihong Huang; Jin Liu; Yurong Xing; Jingjing Cheng (Food Chemistry, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

Multi-objective machine learning for health-oriented O3 and PM2.5 control: Integrating VOC photochemical consumption and source apportionment - Hongyuan Jia; Sen Yao; Xianda Tang; Muqiang Zheng; Yuxuan Dong; Fengjuan Fan; Shushen Yang; Hanyu Zhang (Journal of Hazardous Materials, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Preparation and characterization of curcumin succinyl-glucoside derivative chitosan composite film based on biotransformation and self-assembly technology - Fan Yang; Jiaqi Liu; Nan Wang; Sheng Guo; Jinao Duan; Liangliang Chen; Sen Zhang (Food Hydrocolloids, 2026)

Mechanistic effects of starch-lipid complexes formation on oat starch digestibility during roasting process - Wenhua Ma; Fan Yang; Binghua Sun; Xiaojie Qian; Sen Ma; Chong Liu; Xiaoxi Wang (Carbohydrate Polymers, 2026)

Everything is everywhere, but everywhere is different: evidence from the phylogeography of asexual bdelloid rotifer Rotaria rotatoria species complex - Lingyun Zhu; Rong Huang; Sen Feng; Fan Gao; Meng Li; Hairong Lian; Zhizhong Li; Xinfeng Cheng; Mingbo Yin; Wei Zhang; Yilong Xi; Xianling Xiang (Hydrobiologia, 2026)

Temperature-dependent dopaminergic disruption by chlorpromazine in the rotifer Brachionus calyciflorus: Evidence from receptor gene expression and population response - Sen Feng; Lingyun Zhu; Meng Li; Pengrui Xu; Chuhan Xu; Hairong Lian; Fan Gao; Xinfeng Cheng; Xianling Xiang (Aquatic Toxicology, 2026)

Agricultural cropping practices and fertilization affects microbial activity of dissimilatory nitrate reduction process: insights from metagenomics sequencing and 15N isotopic signatures - Zhen Fan; Yansong Bai; Xiaohong Niu; Xiao Wei; Chengyao Ren; Xinxiong Du; Sen Du; Gehong Wei; Duntao Shu (Plant and Soil, 2026)

Optimizing microbial fuel cells for wastewater treatment: material advances, design strategies, and application frontiers - Sen Wang; Zhiwei Fan; Yanling Guan; Siyu Yi; Lei Yu; Fuping Li; Hao Wang (Environmental Science and Pollution Research, 2025)

Efficient directional biosynthesis of isoquercitrin from quercetin by Bacillus subtilis CD-2 and its anti-inflammatory activity - Ju Han; Jingru Ma; Ruiqi He; Fan Yang; Jingyi Meng; Jiaqi Liu; Fanxing Shi; Jinao Duan; Liangliang Chen; Sen Zhang (Natural Product Research, 2025)

Limited carbon sequestration potential despite enhanced productivity in groundwater-influenced hyper-arid ecosystems - Mengtao Ci; Xingming Hao; Sen Zhang; Fan Sun; Qixiang Liang; Xue Fan; Jingjing Zhang; Xuewei Li; Haibing Xiong (Journal of Hydrology, 2025)

Peripheral blood RNA modifications as a novel diagnostic signature for polycystic ovary syndrome - Liwen Zhang; Xinxin Liu; Yu Zhang; Lang Qin; Shijia Pan; Xueqi Yan; Sen Dong; Zerong Feng; Song-jia Fan; Rusong Zhao; Xueying Gao; Shigang Zhao; et al. (Science China Life Sciences, 2025)

LA-ICP-MS-quantitated boronate affinity magnetic Zr-MOFs prepared via post-modification for glycopeptides enrichment - Feng Zhang; Sen Zhang; Xing Liu; Wei Gao; Jun Luo; Yi-fan Pan; Wei-Juan Zheng; Xin Hu; Hong-zhen Lian (Analytica Chimica Acta, 2025)

Functionalized carbon dots with polydentate ligands for highly stable aqueous zinc ion batteries - Yangming Fan; Jia Zhang; Hanchang Wang; Sen Zhang; Dezhi Kong; Tingting Xu; Shuge Dai; Junmin Xu; Hui Wang; Xinchang Wang; Ye Wang (Chemical Engineering Journal, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

Assessing ozone formation impact through SHAP interaction redistribution analysis: A novel framework for evaluating VOC photochemical loss and source interactions - Sen Yao; Hongyuan Jia; Fengjuan Fan; Na Zhao; Yujia Kuang; Xianda Tang; Qiqian Huang; Xindong Wang (Environmental Impact Assessment Review, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Antitumor activity and mechanistic study of steroidal saponins from the rhizomes of Paris polyphylla var. yunnanensis - Yu Zhang; Yu-Chen Fan; Yu-Chen Zhang; Qing Li; Yun-Yun Su; Chen-Sen Xu; Hao-Lin Yu; Chao Wang; Jing Zhang; Zhi-Xin Liao (Phytochemistry, 2025)

Ultra-stable CO2-aqueous foams for carbon sequestration and internal mineralization in cellular cements - Dingqiang Fan; Xue-Sen Lv; Jian-Xin Lu; Rui Yu; Wei She; Juhyuk Moon; Takafumi Noguchi; Chi Sun Poon (Chemical Engineering Journal, 2025)

Mechanisms of chemical corrosion in alumina-chromite refractories during e-waste recovery via pyrometallurgy - Shiliang Chen; Jian Wu; Xin Wang; Youqi Fan; Yuntao Yan; Xiutao Guan; Zhipeng Guo; Sen Zhao; Wenlong Tan; Chao Ding; Hongming Long (Journal of Environmental Chemical Engineering, 2025)

Advancing autotrophic nitrogen removal in low C/N ratio wastewater: Innovative application of supercapacitor to enhance microbial electrolysis cells - Sen Fan; Yuhan Song; Decong Zheng; Xinyuan Peng; Sitao Li; Ping Gao; Daping Li (Journal of Environmental Sciences, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Polymetallic Te-rich melts contribute to efficient enrichment and precipitation of Au in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ri-Chen Zhong; Sarah A. Gleeson; Zhuo-Sen Yao; Daniel E. Harlov; Xiao-Dong Deng; Hao Cui; Chang Yu; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Inhibition of KDM6B prevents osteoarthritis by blocking growth plate-like H3K27me3 loss in bivalent genes - Hao Du; Yao Zhang; Xi Yu; Xuanhe You; Diwei Wu; Ze Du; Yongrui Cai; Zhenyu Luo; Hanpeng Lu; Zhixin Liao; Bi-Sen Ding; Ya Zhao; et al. (Science China Life Sciences, 2025)

Quantitative impacts of VOC sources on atmospheric oxidation capacity and O3 formation from a megacity in China - Sen Yao; Fengjuan Fan; Hongyuan Jia; Shushen Yang; Junmei Zhang; Hanyu Zhang; Wenjiao Duan (Atmospheric Environment, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Toxicity and intergenerational accumulation effect of tire wear particles and their leachate on Brachionus plicatilis - Hairong Lian; Lingyun Zhu; Chunwang Zha; Meng Li; Sen Feng; Fan Gao; Xin Zhang; Yilong Xi; Xinfeng Cheng; Xianling Xiang (Environmental Pollution, 2025)

Regulation of ROS balance in the tumor microenvironment achieves reversal of immune suppression and deep penetration of nanomedicines - Zichuang Xu; Rongrong Fan; Xuhao Zhang; Yufei Guo; Sen Tan; Yifei Li; Yaqian Yan; Jiajun Gao; Weili Xue; Desong Wang; Dawei Gao (Chemical Engineering Journal, 2025)

Ingenious microfluidic-microwave integrated biosensor for cell sorting and concentration detection of mixed white blood cells and yeasts solution - Yuan-Bo Li; Yan-Xiong Wang; Sen Yang; Qian-Long Chen; Zhong-Hao Li; Jun-Ge Liang; Qi-Gao Fan; Yan-Feng Jiang; Xiaoman Zhou; Tian Qiang (Chemical Engineering Journal, 2025)

Mechanisms and efficiency of CO2 absorption in polyamidoamine dendrimers: Experiments and theoretical calculations - Jialong Yang; Shanshan Dai; Wei Fan; Sen Qin; Ruiyao Wang; Yuanqiang Zhu (Journal of Environmental Chemical Engineering, 2024)

Revealing the interplay of dissolved organic matters variation with microbial symbiotic network in lime-treated sludge landscaping - Zexu Chen; Yu Zhang; Boyuan Yang; Sen Fan; Lanfeng Li; Peng Yang; Weijun Zhang (Environmental Research, 2024)

Experimental studies and pore-scale modeling of hydrate dissociation kinetics at different depressurization rates in a cubic hydrate simulator - Chang-Wen Xiao; Xiao-Sen Li; Hong-Feng Lu; Gang Li; Chen-Lu Xu; Rong-Rong Qi; Dong-Hui Xing; Xian Li; Yi-Fan Weng; Lu Yu (Chemical Engineering Journal, 2024)

Deeply understanding electrocatalytic oxygen evolution reaction from the perspective of defect structures - Huan Wang; Wenlin Fan; Shiduo Yang; Guannan Gong; Sen Chen; Lishi Jiao; Feifei You; Jian Qi (Chemical Engineering Journal, 2024)

Advanced hydrogels for pancreatic fistula prevention, management and treatment: requirements, advances, and prospects - Yajuan He; Shihong Shen; Sen Zhang; Pan Wang; Dan Zeng; Xiaoxuan Ma; Daidi Fan (Chemical Engineering Journal, 2024)

Health benefits of saponins and its mechanisms: perspectives from absorption, metabolism, and interaction with gut - Yu Zhang; Ruojie Hao; Junda Chen; Sen Li; Kai Huang; Hongwei Cao; Mohamed A. Farag; Maurizio Battino; Maria Daglia; Esra Capanoglu; Fan Zhang; Qiqi Sun; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Emerging threat of marine microplastics: Cigarette butt contamination on Yellow Sea beaches and the potential toxicity risks to rotifer growth and reproduction - Hairong Lian; Lingyun Zhu; Meng Li; Sen Feng; Fan Gao; Xin Zhang; Fan Zhang; Yilong Xi; Xianling Xiang (Journal of Hazardous Materials, 2024)

Volatomic differences among Vitis amurensis cultivars and its hybrids with V. vinifera revealed the effects of genotype, region, and vintage on grape aroma - Ming-Yu Li; Xuan-Xuan Pei; Ning Shi; Yi-Ming Yang; Shu-Tian Fan; Yan-Feng Sun; Qing-Sen Kong; Chang-Qing Duan; Keji Yu; Jun Wang (Food Research International, 2024)

Xanthohumol combined with chitosan-oxidized starch film as a potential new strategy for food packaging: Characterization, physicochemical and biological properties - Fan Yang; Siyuan Chang; Lin Zhao; Jing Han; Hao Li; Sen Zhang; Sheng Guo; Jinao Duan (Food Packaging and Shelf Life, 2024)

Water quality assessment and its pollution source analysis from spatial and temporal perspectives in small watershed of Sichuan Province, China - Tao Song; Weiguo Tu; Mingyue Su; Han Song; Shu Chen; Yuankun Yang; Min Fan; Xuemei Luo; Sen Li; Jingjing Guo (Environmental Monitoring and Assessment, 2024)

Spatio-temporal characteristics and multi-scale risk identification of pollution load based on sensitivity analysis in small watersheds located in Tuojiang River Basin, China - Mingyue Su; Min Fan; Tao Song; Yuankun Yang; Shu Chen; Weiguo Tu; Zhuo Li; Sen Li (Environmental Monitoring and Assessment, 2024)

The regulation effect of urban green space on air particulate matter concentration under different matrices in Xi'an city - Bo Jiang; Shiyu Fan; Chang Sun; Sen Mu; Tian Gao; Ling Qiu (Air Quality, Atmosphere & Health, 2024)

A novel zwitterionic magnetic nanocomposite developed for non-invasive speciation analysis of inorganic chromium - Faisal Faiz; Yi-fan Pan; Sen Zhang; Jinxia Dai; Jun-qin Qiao; Hong-zhen Lian; Li Mao; Xiao-bing Cui (Journal of Hazardous Materials, 2024)

Heterometallic Eu/Zn-MOF-based ratiometric sensing platform: Highly sensitive fluorescence / second-order scattering identification of tetracycline analogs and its molecular informatization applications - Ya Jie Fan; Jiang Xue Dong; Tan Liu; Yan Qing Chang; Yong Sen Zhao; Yan Lei Li; Sai Mei Zhang; Song Yun Cao; Ming Su; Shi Gang Shen; Zhong Feng Gao (Analytica Chimica Acta, 2024)

High-efficiency removal of ciprofloxacin by persulfate activated with 3D Bi2WO6/g-C3N4/GA Z-scheme heterojunction under simulated sunlight - Yukun Li; Haiyang Zhang; Sen Yao; Cong Chao; Qishi Chen; Junhua Chen; Fengjuan Fan; Hongyuan Jia; Mingjia Dong (Journal of Water Process Engineering, 2024)

Relationships between high-concentration toxic metals in sediment and evolution of microbial community structure and carbon–nitrogen metabolism functions under long-term stress perspective - Tao Song; Weiguo Tu; Shu Chen; Min Fan; Liang Jia; Bin Wang; Yuankun Yang; Sen Li; Xuemei Luo; Mingyue Su; Jingjing Guo (Environmental Science and Pollution Research, 2024)

Fintech's impact on green productivity in China: Role of fossil fuel energy structure, environmental regulations, government expenditure, and R&D investment - Min Fan; Yun Zhou; Zhixi Lu; Sen Gao (Resources Policy, 2024)

Kinetic studies of the secondary hydrate formation in porous media based on experiments in a cubic hydrate simulator and a new kinetic model - Chang-Wen Xiao; Xiao-Sen Li; Gang Li; Yi-Song Yu; Qiu-Nan Lv; Yang Yu; Yi-Fan Weng; Jian-Wu Liu; Jian-Xing Yu (Fuel, 2024)

Evolution of carbon deposits during ethylene aromatization over Zn/ZSM-5 - Rui Geng; Yacong Liu; Yanxia Guo; Mei Dong; Sen Wang; Weibin Fan; Jianguo Wang; Zhangfeng Qin (Fuel, 2024)

Effects of nitrogen supply on hydrogen-oxidizing bacterial enrichment to produce microbial protein: Comparing nitrogen fixation and ammonium assimilation - Haoran Wang; Lixia Zhang; Chang Tian; Sen Fan; Decong Zheng; Yuhan Song; Ping Gao; Daping Li (Bioresource Technology, 2024)

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

Evaluation and regulation strategy for ecological security in the Tarim River Basin based on the ecological footprint - Jingjing Zhang; Xingming Hao; Xuewei Li; Xue Fan; Sen Zhang (Journal of Cleaner Production, 2024)

High-efficiency process of aluminum removal from rare earth solutions using a readily industrialized ionic liquid - Nian Zhang; Fujian Li; Haiyang Xue; Zhongzhi Wang; Sen Qiu; Bangyu Fan; Yanyan Cheng; Xiangping Zhang (Hydrometallurgy, 2024)

Back-arc suture zone along the north margin of the eastern Cimmerian continent - Shifeng Wang; Shengting Zhang; Suoya Fan; Yiduo Liu; Sen Wang; Licai Song (Lithos, 2023)

Highly effective synthesis of 5-hydroxymethylfurfural from lignocellulosic biomass over a green and one-pot reaction in biphasic system - Quang Tam Huynh; Chong-Ting Zhong; Qing Huang; Yuan-Chung Lin; Ku-Fan Chen; Chien-Sen Liao; Cheng-Di Dong; Ken-Lin Chang (Bioresource Technology, 2023)

Effects of supplementation of cryopreservation media with cysteine on the post-thaw quality and fertility of brown-marbled grouper (Epinephelus fuscoguttatus) spermatozoa - Sen Yang; Bin Fan; Xinghan Chen; Zining Meng (Theriogenology, 2023)

The elevated toxicity of the biodegradation product (guanylurea) from metformin and the antagonistic pattern recognition of combined toxicity: Insight from the pharmaceutical risk assessment and the simulated wastewater treatment - Fan Gao; Hao Wen; Sen Feng; Meng Li; Lingyun Zhu; Yongzhi Zhang; Yilong Xi; Xianling Xiang (Science of The Total Environment, 2023)

Study on the effect of bubble number on the collapse of a multi-bubble system near the rigid wall - Sen Han; Yaxin Huang; Wenwei Fan; Qiyan Wang; Tinglin Huang; Yu Li (Ocean Engineering, 2023)

Air pollution characteristics, health risks, and typical pollution processes in autumn and winter in a central city of China - Qianheng Wang; Sen Yao; Jie Tao; Yifei Xu; Huijiao Yan; Hanyu Zhang; Shushen Yang; Fengjuan Fan (Air Quality, Atmosphere & Health, 2023)

miRNAs contributing to the repair of tendon injury - Kexin Lyu; Xinyue Liu; Tianzhu Liu; Jingwei Lu; Li Jiang; Yixuan Chen; Longhai Long; Xiaoqiang Wang; Houyin Shi; Fan Wang; Sen Li (Cell and Tissue Research, 2023)
Tendon injury is one of the most common disorders of the musculoskeletal system, with a higher likelihood of occurrence in elderly individuals and athletes. In posthealing tendons, two undesirable consequences, tissue fibrosis and a reduction in mechanical properties, usually occur, resulting in an increased probability of rerupture or reinjury; thus, it is necessary to propose an appropriate treatment. Currently, most methods do not sufficiently modulate the tendon healing process and restore the function and structure of the injured tendon to those of a normal tendon, since there is still inadequate information about the effects of multiple cellular and other relevant signaling pathways on tendon healing and how the expression of their components is regulated. microRNAs are vital targets for promoting tendon repair and can modulate the expression of biological components in signaling pathways involved in various physiological and pathological responses. miRNAs are a type of noncoding ribonucleic acid essential for regulating processes such as cell proliferation, differentiation, migration and apoptosis; inflammatory responses; vascularization; fibrosis; and tissue repair. This article focuses on the biogenesis response of miRNAs while presenting their mechanisms in tendon healing with perspectives and suggestions.

A new aeolian activity proxy based on analysis of the grain size characteristics of surface soils across the Tengger Desert, northwest China, and its application to a Quaternary aeolian succession - Bing Liu; Hui Zhao; Fan Yang; Aiming Liang; Aijun Sun; Qinghe Niu; Sen Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Bamboo-based magnetic activated carbon for efficient removal of sulfadiazine: Application and adsorption mechanism - Fan Yang; Can Jin; Sen Wang; Yujie Wang; Lu Wei; Longhui Zheng; Haiping Gu; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Chemosphere, 2023)

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Dietary aromatase inhibitor treatment converts XY gsdf homozygous mutants to sub-fertile male in Nile tilapia (Oreochromis niloticus) - Sen Fan; Hong-Juan Shi; You-Xing Peng; Yuan-Qing Huang; Mou-Yan Jiang; Guang-Li Li; De-Shou Wang; Dong-Neng Jiang (Aquaculture, 2023)

Characteristics of summertime ambient volatile organic compounds in Beijing: Composition, source apportionment, and chemical reactivity - Sen Yao; Fengjuan Fan; Junmei Zhang; Qianheng Wang (Atmospheric Pollution Research, 2023)

Chemical weathering processes impacted by pyrite oxidation in the upper Indus River basin, Western Himalaya - Mohd Aadil Bhat; Sen Xu; Daidu Fan; Tanveer Dar; Si-Liang Li (Journal of Asian Earth Sciences, 2023)

Development and catalytic mechanism of a highly efficient Pt/Kβ catalyst for n-Heptane aromatization - Qiuming Zhou; Yanyan Chen; Sheng Fan; Sen Wang; Zhangfeng Qin; Mei Dong; Jianguo Wang; Weibin Fan (Fuel, 2023)

Research on a classification model of loess seismic landslides based on random forest in the Haiyuan region - Ranke Fang; Sen Zhang; Longsheng Deng; Wen Fan; Hao Wang (Bulletin of Engineering Geology and the Environment, 2023)

Key factors controlling the kinetics of secondary hydrate formation in the porous media - Chang-Wen Xiao; Xiao-Sen Li; Gang Li; Yang Yu; Yi-Fan Weng; Qiu-Nan Lv; Jian-Xing Yu (Gas Science and Engineering, 2023)

Studies on micromorphology and permeability of hydrate-bearing porous media - Gang Li; Yi-Fan Weng; Xiao-Sen Li; Ze-Lin Xu; Qiu-Nan Lv; Chun-Gang Xu (Fuel, 2023)

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Rare disperse elements in epithermal deposit: Insights from LA–ICP–MS study of sphalerite at Dalingkou, South China - Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Guo-Guang Wang; Jun-Ying Ding; Shu-Wu Chu; Wen-Sheng Li; Wen-Qing Huang; Ren-Zhi Zhu; Zhe Chi (Journal of Geochemical Exploration, 2023)

Insight into induction period of methanol conversion reaction: Reactivity of ethene-precursors over H-ZSM-5 zeolite is independent of Brϕnsted acid site density - Tingyu Liang; Jialing Chen; Zhangfeng Qin; Sen Wang; Pengfei Wang; Fang Jin; Mei Dong; Jianguo Wang; Weibin Fan (Fuel, 2023)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Noninvasive oral cancer screening based on local residual adaptation network using optical coherence tomography - Wei Yuan; Long Cheng; Jinsuo Yang; Boya Yin; Xingyu Fan; Jing Yang; Sen Li; Jianjun Zhong; Xin Huang (Medical & Biological Engineering & Computing, 2022)

A First Insight Into the Heat-Induced Changes in Proteomic Profiles of the Coral Symbiotic Bacterium Endozoicomonas montiporae - Ya-Fan Chan; Chia-Yu Chen; Chih-Ying Lu; Yung-Chi Tu; Kshitij Tandon; Shinya Shikina; Sen-Lin Tang (Frontiers in Marine Science, 2022)
Endozoicomonas , a core bacterial group in corals, may also be a coral symbiont. Endozoicomonas communities often decrease rapidly in corals under heat stress. However, how the bacteria respond to changes in temperature and coral host during heat stress is unknown. Here, we employed the cultivable, dominant species E. montiporae as a working organism to explore how Endozoicomonas responds to heat stress. We designed two experiments to clarify the extent to which E. montiporae is influenced by temperature and coral host. We detected differentially expressed protein (DEP) profiles in this bacterium at 31 and 33°C compared to 25°C by tandem mass tags-based quantitative proteome analysis. Fifty DEPs, including many heat shock proteins, were detected when the temperature changed. The expression of antioxidant defense proteins and key pyruvate synthase proteins decreased, suggesting that E. montiporae were in a physiology of stress at 33°C. Furthermore, some proteins were differentially expressed because of the heat-stress-treated coral lysate specifically, suggesting that not only heat but also heat-induced host factors can affect the protein expression of the bacterium. This study provides an in-depth analysis of how the molecular mechanisms of Endozoicomonas are affected by heat stress and coral host.

Identification of groundwater microbial communities and their connection to the hydrochemical environment in southern Laizhou Bay, China - Fan Yang; Sen Liu; Chao Jia; Yujue Wang (Environmental Science and Pollution Research, 2022)

Negative‐pressure irrigation improves water and fertilizer use efficiencies and fruit yield of greenhouse tomato on the North China Plain* - Yinkun Li; Xuzhang Xue; Fan Xu; Wenzhong Guo; Minjie Duan; Sen Lin; Youli Li; Zhan Wang (Irrigation and Drainage, 2021)
Water and fertilizer supply are the main factors limiting greenhouse vegetable production on the North China Plain. This study tested the hypothesis that negative‐pressure irrigation is advantageous for reducing water and fertilizer application compared with drip irrigation in a greenhouse. Three treatments (drip irrigation + optimal fertilizer [DOF], drip irrigation + Yamazaki tomato nutrient solution [DNS], and negative‐pressure irrigation + Yamazaki tomato nutrient solution [NNS]) were applied in a greenhouse tomato double‐cropping system conducted in consecutive spring–summer and autumn–winter seasons. Soil moisture content, nitrate‐nitrogen (N) concentration, fruit yield, total N uptake ( N u ), irrigation water productivity, and partial factor productivity of applied fertilizer were analysed. The seasonal variation of soil moisture and nitrate‐N contents in the 0–20‐cm soil layer for NNS treatment was stable. Nitrate‐N accumulated after the final harvest in the autumn–winter season of NNS treatment was significantly less than under DOF and DNS. Despite lower water and nutrient inputs, NNS showed higher N u and fruit yield than DOF and DNS. These results demonstrated that negative‐pressure irrigation can reduce irrigation water and nutrient inputs and nitrate‐N accumulation in the soil, and significantly improve water and fertilizer use efficiency in greenhouse‐grown tomato compared with those under drip irrigation.

Corrigendum: The Effects of Storage in vitro on Functions, Transcriptome, Proteome, and Oxidation Resistance of Giant Grouper Sperm - Yang Yang; Tong Wang; Sen Yang; Xi Wu; Wenhua Huang; Bin Fan; Junhong Xia; Zining Meng; Xiaochun Liu (Frontiers in Marine Science, 2021)

Optimization design of a honeycomb-hole submarine pipeline under a hydrodynamic landslide impact - Xing-sen Guo; Ting-kai Nian; Ning Fan; Yong-gang Jia (Marine Georesources & Geotechnology, 2021)

First report of leaf spot on Prunus salicina caused by Alternaria alternata in China - Haijiang Long; Sen Yang; Xianhui Yin; Zhibo Zhao; Youhua Long; Juan Fan; Ran Shu; Guifei Gu (Journal of Plant Pathology, 2021)

The Effects of Storage in vitro on Functions, Transcriptome, Proteome, and Oxidation Resistance of Giant Grouper Sperm - Yang Yang; Tong Wang; Sen Yang; Xi Wu; Wenhua Huang; Bin Fan; Junhong Xia; Zining Meng; Xiaochun Liu (Frontiers in Marine Science, 2021)
Asynchrony of sexual maturity is a huge limitation in the reproduction of grouper sperm. Cold storage of sperm is an effective method to solve the problem of asynchronization. However, sperms gradually lose their activity with the prolonged storage time in vitro . In order to explore causes, the effects of cold storage on transcriptome, proteome and oxidation resistance of giant grouper sperm were analyzed. Firstly, the absolute RNA quantity and consistent transcripts existed in each spermatozoon were estimated. With the prolonged storage, the RNA quantity gradually decreased both in the cytoplasm and in the mitochondria of the spermatozoon. The decreased transcripts were mainly enriched with energy metabolism and stress response. Similar to RNAs, the absolute protein quantity was also significantly decreased during the storage of sperm. Decreased proteins were mainly enriched with the oxidative phosphorylation pathway. Proteins involved in the oxidative phosphorylation showed a faster degradation rate compared to the average total protein. In addition, the oxidation resistance and adenosine triphosphate (ATP) contents showed a significant decrease in the sperm during storage in vitro . These results implied that damages of transcriptome, proteome, and oxidation resistance have negative effects on the normal functions of sperm, especially their energy metabolism. The present study provides essential foundation for improving the storage of sperm in vitro .

Cd Adsorption by Iron–Organic Associations: Implications for Cd Mobility and Fate in Natural and Contaminated Environments - Yijie Mao; Weiguo Fan; Yaxin Yan; Wu Xiang; Shenghong Hu; Sen Yan (Bulletin of Environmental Contamination and Toxicology, 2021)

Cryopreservation of sperm in brown-marbled grouper (Epinephelus fuscoguttatus) - Sen Yang; Bin Fan; Xinghan Chen; Zining Meng (Aquaculture International, 2020)

Microstructure analysis on the dynamic behavior of marine clay in the South China Sea - Ting-kai Nian; Hou-bin Jiao; Ning Fan; Xing-sen Guo (Marine Georesources & Geotechnology, 2020)

Erratum to: Exosome-derived galectin-9 may be a novel predictor of rejection and prognosis after liver transplantation - Ai-bin Zhang; Yi-fan Peng; Jun-jun Jia; Yu Nie; Shi-yu Zhang; Hai-yang Xie; Lin Zhou; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2020)

Resource availability affects temporal variation of phytoplankton size structure in the Kuroshio east of Taiwan - Fan‐Sian Lin; Pei‐Chi Ho; Akash R. Sastri; Chung‐Chi Chen; Gwo‐Ching Gong; Sen Jan; Chih‐hao Hsieh (Limnology and Oceanography, 2020)
The on‐going discussion concerning how environmental factors determine phytoplankton size structure has centered around two hypotheses: (H1) The resource‐size relationship predicts that normalized biovolume size spectrum (NBSS) slopes for phytoplankton are progressively shallower with increasing resource availability and (H2) The temperature‐size relationship predicts that phytoplankton NBSS slopes steepen with increasing water temperature. To test these hypotheses, we examined 72 phytoplankton assemblage collections in the Kuroshio east of Taiwan. Total phytoplankton biomass was used as a proxy for resource availability instead of nutrients because nutrients are depleted and do not represent resource availability for oligotrophic seas. We found no significant relationship between NBSS slopes with temperature, providing little support for the temperature‐size rule. In contrast, a positive relationship between NBSS slopes and total biomass for most of the year lends general support to the resource‐size relationship, except during the winter and early spring. To explain this exception, we hypothesize that resource pulses occurring during the cold seasons are used more efficiently by small cells and promote faster growth of small relative to large phytoplankton because these pulses take place after a long period of resource depletion in oligotrophic seas; thus, the NBSS slopes become much steeper than would be expected from a positive resource‐size relationship. This deviation can be considered as nonsteady state in terms of phytoplankton size structure relative to resources. Nevertheless, we cannot rule out the possibility that grazing effects also play an important role in controlling phytoplankton size structure.

Exosome-derived galectin-9 may be a novel predictor of rejection and prognosis after liver transplantation - Ai-bin Zhang; Yi-fan Peng; Jun-jun Jia; Yu Nie; Shi-yu Zhang; Hai-yang Xie; Lin Zhou; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2019)

Rapid and Sparse Labeling of Neurons Based on the Mutant Virus-Like Particle of Semliki Forest Virus - Fan Jia; Xutao Zhu; Pei Lv; Liang Hu; Qing Liu; Sen Jin; Fuqiang Xu (Neuroscience Bulletin, 2019)

An H-ferritin from the hydrothermal vent shrimp Rimicaris exoculata and its potential role in iron metabolism - Xiao-Li Liu; Sen Ye; Hua-Wei Li; Bo Lu; Yan-Qin Yu; Yu-Peng Fan; Wei-Jun Yang; Jin-Shu Yang (BioMetals, 2019)

Monitoring and analysis of mining 3D time-series deformation based on multi-track SAR data - Meinan Zheng; Kazhong Deng; Hongdong Fan; Sen Du; Hao Zou (International Journal of Remote Sensing, 2019)

Clinical pharmacodynamics and long-term efficacy of Talcom vs. Plavix in patients undergoing coronary stent implantation: a randomized study with 5-year follow-up - Jinshuang Li; Yuansheng Fan; Tiantian Zhu; Jun Chen; Deyu Kong; Haoyu Meng; Jing Zhang; Ke Xu; Sen Ye; Yuqin Ji; Chunjian Li (European Journal of Clinical Pharmacology, 2018)

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease - Jiaqi Liu; Yangzhong Zhou; Sen Liu; Xiaofei Song; Xin-Zhuang Yang; Yanhui Fan; Weisheng Chen; Zeynep Coban Akdemir; Zihui Yan; Yuzhi Zuo; Renqian Du; Zhenlei Liu; et al. (Human Genetics, 2018)

Enhanced production of fructosyltransferase in Aspergillus oryzae by genome shuffling - Shenghai Wang; Mengjie Duan; Yalan Liu; Sen Fan; Xiaoshan Lin; Yi Zhang (Biotechnology Letters, 2017)

Ecological status classification of the Taizi River Basin, China: a comparison of integrated risk assessment approaches - Juntao Fan; Elena Semenzin; Wei Meng; Elisa Giubilato; Yuan Zhang; Andrea Critto; Alex Zabeo; Yun Zhou; Sen Ding; Jun Wan; Mengchang He; Chunye Lin (Environmental Science and Pollution Research, 2015)

A multi-proxy reconstruction of spatial and temporal variations in Asian summer temperatures over the last millennium - Feng Shi; Quansheng Ge; Bao Yang; Jianping Li; Fengmei Yang; Fredrik Charpentier Ljungqvist; Olga Solomina; Takeshi Nakatsuka; Ninglian Wang; Sen Zhao; Chenxi Xu; Keyan Fang; et al. (Climatic Change, 2015)

Identification of Two Cucumber Putative Silicon Transporter Genes in Cucumis sativus - Hua-Sen Wang; Chao Yu; Pei-Pei Fan; Bin-Fu Bao; Tao Li; Zhu-Jun Zhu (Journal of Plant Growth Regulation, 2015)

Decreased miR-30b-5p expression by DNMT1 methylation regulation involved in gastric cancer metastasis - Fengchang Qiao; Kun Zhang; Pihai Gong; Ling Wang; Jiaojiao Hu; Sen Lu; Hong Fan (Molecular Biology Reports, 2014)

Combined effect of five single nucleotide polymorphisms related to IL23/Th17 pathway in the risk of psoriasis - Xianyong Yin; Hui Cheng; Ran Zhang; Xing Fan; Fusheng Zhou; Long Jiang; Xianfa Tang; Gang Chen; Xianbo Zuo; Xiaodong Zheng; Sen Yang; Xuejun Zhang (Immunogenetics, 2014)

Gestational Hypoxia Induces Sex-Differential Methylation of Crhr1 Linked to Anxiety-like Behavior - Xi Wang; Fan-Sen Meng; Zong-Yun Liu; Jun-Ming Fan; Ke Hao; Xue-Qun Chen; Ji-Zeng Du (Molecular Neurobiology, 2013)

Seasonal variation of diet and time budget of Eastern hoolock gibbons (Hoolock leuconedys) living in a northern montane forest - Peng-Fei Fan; Huai-Sen Ai; Han-Lan Fei; Dao Zhang; Sheng-Dong Yuan (Primates, 2013)

DNMT3A rs36012910 A>G polymorphism and gastric cancer susceptibility in a Chinese population - Qunying Wu; Sen Lu; Ling Wang; Jiaojiao Hu; Fengchang Qiao; Xuemei Qiu; Chengcheng Zhao; Yingbin Lao; Yunwei Song; Hong Fan (Molecular Biology Reports, 2012)

Folic acid inhibits endothelial cell proliferation through activating the cSrc/ERK 2/NF-κB/p53 pathway mediated by folic acid receptor - Shyr-Yi Lin; Woan-Ruoh Lee; Yi-Fan Su; Sung-Po Hsu; Hsu-Chen Lin; Pei-Yin Ho; Tien-Chi Hou; Yu-Pei Chou; Chun-Ting Kuo; Wen-Sen Lee (Angiogenesis, 2012)

Isolation and performance evaluation of halotolerant phosphate solubilizing bacteria from the rhizospheric soils of historic Dagong Brine Well in China - Wen-liang Xiang; Hua-zhong Liang; Sen Liu; Fan Luo; Jie Tang; Ming-yuan Li; Zhen-ming Che (World Journal of Microbiology and Biotechnology, 2011)

Three novel SNPs in the coding region of PPARγ gene and their associations with meat quality traits in cattle - Yue Yuan Fan; Lin Sen Zan; Chang Zhen Fu; Wan Qiang Tian; Hong Bao Wang; Yan Yan Liu; Ya Ping Xin (Molecular Biology Reports, 2011)